Relative Sinus Bradycardia: An Unexpected Finding in Preeclampsia With Acute Pulmonary Edema - Angsubhakorn, Natthapon (Cureus, 2021)
Preeclampsia is a multifactorial pregnancy-specific syndrome, which can result in significant alterations in cardiovascular hemodynamics. We report an observation of unexpected relative bradycardia in a previously healthy woman who presented with postpartum preeclampsia and acute pulmonary edema. We observed an increase in heart rate following normalization of blood pressure, which suggested that the initial slower than expected heart rate may reflect a baroreceptor response to hypertension. Whether this finding should be regarded as a severe aspect of the disease spectrum needs further study.